Sociology in Mexico An Intellectual and Institutional History - Zabludovsky, Gina (Sociology Transformed, 2024)
This open access book presents a condensed history of Sociology in Mexico from its origins, through to the middle of the 19th century and up to the present day. The book analyses the interaction between sociology and the main economic, political and social change in the country, including the 1910 Mexican Revolution, the main social movements, the role of the intellectual exiles from Spain and Latin America, and the participation of women, who have often remained invisible in the history of sociology. The book explores how sociological discourse played a fundamental role in the separation of secular and public education and the search for a 'national project' from 1868 onwards, despite the lack of an institute of social research until 1930; how sociology became an autonomous social science, led by a few intellectuals and public figures, as it became institutionalized in universities, and the effect this had on the development of the discipline; the influence of Marxism during the 1970s; and the progression from a process of specialization after the fall of the Berlin Wall to a new trend of working in collective projects with an increasing interdisciplinary perspective in the first decades of the 21st century.